Ultra wideband antenna for microwave imaging using modified fractal structure - Qasem Rasheda, Hamid Mohammed (2017)
Since the Federal Communication Commission release of bandwidth of 7.5 GHz (from 3.1 GHz to 10.6 GHz) for ultra wideband application (UWB), UWB is rapidly advancing as a high data rate wireless technology. Moreover, there are more challenges in designing a UWB antenna than a narrow band antenna. A suitable UWB antenna should be capable of operating over an ultra wide bandwidth as allocated by the FCC. In addition, satisfactory radiation properties over the whole frequency range are necessary as well. This project presents the design with fractal geometry of an UWB patch antenna. To achieve UWB characteristic, a planer antenna is considered for the design purpose. The configuration of designed antenna consisted of a partial ground and the patch with addition of two stairs in its bottom edge connected with the feed line. The antenna was designed and optimized using CST Microwave Studio 2014. The proposed antenna is optimized to achieve a fractal shape by introducing slots in the patch at various positions with half grounded structure. A compact design has been observed as a result of optimization. Moreover, the results have been analysed to get the desired bandwidth, and for the comparison purpose the antenna design has been fabricated using FR-4 dielectric substrate and measured its scattering parameters using vector network analyzer (VNA). The obtained results from the measurement have the bandwidth ranges from 2.2 GHz to 12GHz. The analysis of simulated and measured results shows a little deviation due to fabrication and coaxial cable losses.